Targeted capture and sequencing of Orientia tsutsugamushi genomes from chiggers and humans - Elliott, I; Thangnimitchok, N; de Cesare, M; Linsuwanon, P; Paris, DH; Day, NPJ; Newton, PN; Bowden, R; Batty, EM (Elsevier, 2021)
Scrub typhus is a febrile disease caused by Orientia tsutsugamushi, transmitted by larval stage Trombiculid mites (chiggers), whose primary hosts are small mammals. The phylogenomics of O. tsutsugamushi in chiggers, small mammals and humans remains poorly understood. To combat the limitations imposed by the low relative quantities of pathogen DNA in typical O. tsutsugamushi clinical and ecological samples, along with the technical, safety and cost limitations of cell culture, a novel probe-based target enrichment sequencing protocol was developed. The method was designed to capture variation among conserved genes and facilitate phylogenomic analysis at the scale of population samples. A whole-genome amplification step was incorporated to enhance the efficiency of sequencing by reducing duplication rates. This resulted in on-target capture rates of up to 93% for a diverse set of human, chigger, and rodent samples, with the greatest success rate in samples with real-time PCR Ct values below 35. Analysis of the best-performing samples revealed phylogeographic clustering at local, provincial and international scales. Applying the methodology to a comprehensive set of samples could yield a more complete understanding of the ecology, genomic evolution and population structure of O. tsutsugamushi and other similarly challenging organisms, with potential benefits in the development of diagnostic tests and vaccines.